2007
DOI: 10.1523/jneurosci.0396-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Polysialylated Neural Cell Adhesion Molecule in the Dorsal Hippocampus after Contextual Fear Conditioning Is Involved in Long-Term Memory Formation

Abstract: The role of the hippocampus in pavlovian fear conditioning is controversial. Although lesion and pharmacological inactivation studies have suggested a key role for the dorsal hippocampus in contextual fear conditioning, the involvement of the ventral part is still uncertain. Likewise, the debate is open with regard to the putative implication of each hippocampal subdivision in fear conditioning to a discrete conditioned stimulus. We explored the potential existence of dissociations occurring in the dorsal vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 83 publications
4
58
1
1
Order By: Relevance
“…Although heterosynaptic LTD has recently been shown to require homosynaptic activity (Abraham et al, 2007), we would like to note that the expression of PSA following homosynaptic LTD may differ from our present results in heterosynaptic LTD. In light of the data showing that PSA-NCAM increases in the DG following fear conditioning, odour discrimination or spatial learning (Fox et al, 1995;Foley et al, 2003;Venero et al, 2006;Lopez-Fernandez et al, 2007), and that impairing or promoting PSA-NCAM function accordingly affect learning (Florian et al, 2006;Markram et al, 2007), we raise the question of whether the increase in PSA observed after learning represents another form of plasticity which acts synergistically with LTP or LTD.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Although heterosynaptic LTD has recently been shown to require homosynaptic activity (Abraham et al, 2007), we would like to note that the expression of PSA following homosynaptic LTD may differ from our present results in heterosynaptic LTD. In light of the data showing that PSA-NCAM increases in the DG following fear conditioning, odour discrimination or spatial learning (Fox et al, 1995;Foley et al, 2003;Venero et al, 2006;Lopez-Fernandez et al, 2007), and that impairing or promoting PSA-NCAM function accordingly affect learning (Florian et al, 2006;Markram et al, 2007), we raise the question of whether the increase in PSA observed after learning represents another form of plasticity which acts synergistically with LTP or LTD.…”
Section: Discussionmentioning
confidence: 94%
“…Whereas behavioural studies have found increases in PSA-NCAM in the DG after training (Fox et al, 1995;Foley et al, 2003;Venero et al, 2006;Lopez-Fernandez et al, 2007), no study to date has examined whether LTP or LTD would also produce changes in PSA-NCAM in the DG. Therefore, we sought to examine this issue in vivo in the awake rat.…”
Section: O B J E C T I V E Smentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel, there was a similar stressful-learning-induced synaptic increase in Ncadherin (a cell-adhesion molecule that interacts with GluA2 subunits and which plays an important role in the formation and growth of dendritic spines [45]). Although this result is purely correlative, it suggests a potential interaction between these two molecules as a mechanism whereby stress can improve memory function (but note that other synaptic cell-adhesion molecules that are also enhanced after stressful learning paradigms could also be involved [46][47][48]). …”
Section: [ ( ) T D $ F I G ]mentioning
confidence: 87%
“…PSA-NCAM is expressed principally in cells at the subgranular zone (SGZ)-granule cell layer (GCL) interface, representing recently formed and plastic neurons [20,21], with expression also in fibers extending through the GCL into the molecular layer, and a smaller amount on fibers in the hilus. Polysialylation of cell-surface NCAM, which may decrease its homotypic adhesiveness, increases with training [22], and has been implicated in hippocampal memory consolidation in several studies [23][24][25].…”
Section: Introductionmentioning
confidence: 99%